The concurrent validity and reliability of the My Jump Lab smartphone app for the real-time measurement of vertical jump performance - Sentürk, D.; Yüksel, O.; Akyildiz, Z. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The present study had two main objectives: (i) to assess the concurrent validity and agreement of real-time measurement of counter-movement jump (CMJ) height using the My Jump Lab (MJL) mobile application in comparison to a force plate and (ii) to evaluate the intra-session reliability and agreement of the force plate and the MJL application. This cross-sectional investigation involved 36 recreationally active, healthy men (mean age = 22.2 ± 2.9 years) who performed five CMJ repetitions on the force plate with a 2-min rest period. Their jump heights were concurrently recorded using both the force plate and the MJL application. The high validity between the two methods intraclass correlation coefficient >0.984) was observed for all cases. There was a nearly perfect correlation (r = 0.968, p = 0.001, in all cases) between the force plate and MJL application, with very good agreement and a mean difference of 1.016 cm (95% confidence interval: -1.229 to -0.803 cm). High intra-session reliability was observed in the force platform (SEM, 0.42 cm; CV, 1.21%; MDC, 1.5; SWC, 1.12), and MJL (SEM, 0.43 cm; CV, 1.23%; MDC, 1.20; SWC, 1.17). The results demonstrate that the MJL application is a valid and reliable tool for measuring jump performance in real-time and assessing CMJ height.